Time management as a dimension of information literacy - Gómez-Hernández, José-Antonio (Anuario ThinkEPI, 2013)
The aim is to propose that libraries include courses on "Time management skills" within their educational and information literacy services. We consider that users need these skills because of several factors that force us to spend too much time in informational processes, including the excess of content, our habit of 24/7 connectivity, the excess of tasks to be done, and the ubiquity of information. Finally, we suggest some of the issues to be included in the training: skills and tools that help to organize time, and especially attitudes and values to decide how, when and how to spend time on the demands of information and communication.
Keywords: Information literacy; Time management skills.